Permodelan Perkuatan Stabilitas Lereng Menggunakan Analisis Kesetimbangan Batas Dan Metode Elemen Hingga (Studi Kasus : Desain Dinding Penahan Tanah Gitet 275 Kv Substation Betung). - Panca Putra, M Sang Gumilar; Syafawi, Ahmad (Jurnal Ilmiah Poli Rekayasa, 2023)
The increasing national energy demand is influencing the presence of existing power plants. South Sumatra is a region contributing to the national energy supply, leading to the expansion of facilities to generate electricity. Consequently, a new transmission line will be constructed at the 275 KV Betung Station in South Sumatra. With the need to enhance distribution capacity by adding new transmission lines, there is a requirement to expand the area of the Gitet, which was previously 183x98 m2, to 138.55 x 152.68 m2. This study aims to analyze the stability of the embankment, estimated to have an initial height of 8.5 meters. Additionally, plans will be made for constructing retaining walls to expand the Gitet Substation Betung area. Slope Stability Analysis will be conducted using limit equilibrium and finite element methods. The limit equilibrium analysis will employ the Fellenius method, while the Finite Element Method will use Plaxis software. From the analysis results, it's determined that a Retaining Wall (RW) is needed to stabilize the embankment. The design for slope stability involves a 6 meter high counterfort Retaining Wall equipped with Bored Piles having a diameter of 60 cm and a length of 22 meters for every 2.15 meters along the RW alignment.